The relationship of prenatal antibiotic exposure and infant antibiotic administration with childhood allergies: a systematic review - Baron, Ruth (BMC Pediatr, 2020)
BACKGROUND: Early antibiotic exposure may be contributing to the onset of childhood allergies. The main objective of this study was to conduct a systematic review on the relationship between early life antibiotic exposure and childhood asthma, eczema and hay fever. METHODS: Pubmed and Embase were searched for studies published between 01-01-2008 and 01-08-2018, examining the effects of (1) prenatal antibiotic exposure and (2) infant antibiotic administration (during the first 2 years of life) on childhood asthma, eczema and hay fever from 0 to 18 years of age. These publications were assessed using the Newcastle Ottawa Scale (NOS) and analysed narratively. RESULTS: (1) Prenatal antibiotics: Asthma (12 studies): The majority of studies (9/12) reported significant relationships (range OR 1.13 (1.02–1.24) to OR 3.19 (1.52–6.67)). Three studies reported inconsistent findings. Eczema (3 studies): An overall significant effect was reported in one study and in two other studies only when prenatal antibiotic exposure was prolonged. (2) Infant antibiotics: Asthma (27 studies): 17/27 studies reported overall significant findings (range HR 1.12 (1.08–1.16) to OR 3.21 (1.89–5.45)). Dose-response effects and stronger effects with broad-spectrum antibiotic were often reported. 10/27 studies reported inconsistent findings depending on certain conditions and types of analyses. Of 19 studies addressing reverse causation or confounding by indication at least somewhat, 11 reported overall significant effects. Eczema (15 studies): 6/15 studies reported overall significant effects; 9 studies had either insignificant or inconsistent findings. Hay fever (9 studies): 6/9 reported significant effects, and the other three insignificant or inconsistent findings. General: Multiple and broad-spectrum antibiotics were more strongly associated with allergies. The majority of studies scored a 6 or 7 out of 9 based on the NOS, indicating they generally had a medium risk of bias. Although most studies showed significant findings between early antibiotic exposure and asthma, the actual effects are still unclear as intrapartum antibiotic administration, familial factors and confounding by maternal and child infections were often not addressed. CONCLUSIONS: This review points to a moderate amount of evidence for a relationship between early life antibiotics (especially prenatal) and childhood asthma, some evidence for a relationship with hay fever and less convincing evidence for a relationship with eczema. More studies are still needed addressing intra-partum antibiotics, familial factors, and possible confounding by maternal and childhood infections. Children exposed to multiple, broad-spectrum antibiotics early in life appear to have a greater risk of allergies, especially asthma; these effects should be investigated further.